Reading Habit of Librarians Participating in Ix Refresher Course (2007) in University of Kerala, Thiruvananthpuram - Krishna, K. M. (Journal of Information and Knowledge, 2013)
Presents results of a survey of the reading habits of librarians attending a refresher course. Newspapers wer found to the most favoured reading material.